Reflection of Indian culture: A review - Singh, Dr Amitosh (Innovative Research Thoughts, 2017)
The beginning of Indian culture is yet to be known properly as it the oldest culture in the world. The Indian culture grew with diversity and firmness. However, youth of new India is getting attracted towards western culture. This paper reviews various aspects of Indian culture and differentiates it with western culture. The significance and authenticity of the Indian culture will be reviewed and will also attempt to search for better approaches to explain its importance to the youth.